The Role Of Teacher Performance In Mediating Leadership, Organizational Climate, And Motivation In The Quality Of Vocational School Education In Sabang City - Fajar Rejeki Ananda Lubis (SEAN Institute, 2024)
This study aims to investigate the impact of teacher performance on the quality of vocational high school (SMK) education in Sabang City in the context of leadership, organizational climate, and motivation. This research uses a quantitative approach and collects data through questionnaires distributed to vocational school teachers in the area. The study focuses on key variables such as teacher performance, the leadership style implemented in the school, the current organizational climate, teacher motivation, and the quality of education. DWe conducted data analysis using structural equation modeling (SEM) analysis to identify direct and indirect effects. he research results show that leadership, organizational climate, and motivation have a significant influence on teacher performance and education quality. We hope that the implications of this research can guide school management and related stakeholders to enhance the quality of education by optimizing the role of teacher performance and increasing supporting factors.